Awareness and Familiarity with AI Writing Tools Among Media Students - Narayan, Satya (Cipta Pustaka Nusantara, 2024)
This study investigates the level of awareness and familiarity with AI writing tools among students in the Department of Media at Maharishi University of Information Technology. A mixed-methods approach, combining a descriptive survey and semi-structured interviews, was used to gather quantitative and qualitative data from 200 students. The survey results revealed that 72% of students were aware of AI writing tools like Grammarly, Quillbot, and ChatGPT, but their familiarity and usage varied. While 61% of students had used these tools at least once, only 15% reported frequent use, and 39% had never used them. Most students perceived AI writing tools as beneficial for improving writing skills and saving time, yet 42% expressed concerns about over-reliance, potentially hindering independent learning. Qualitative insights from interviews highlighted that peer influence and coursework were primary sources of awareness, and while students valued these tools for enhancing grammar and clarity, they also raised ethical concerns about excessive dependency. The findings suggest a need for educational institutions to provide clear guidelines and training on the ethical use of AI writing tools to enhance digital literacy without compromising academic integrity. The study's limitations include its focus on a single department, which may affect generalizability. Future research could explore the impact of AI writing tools across various disciplines and assess the long-term effects on students' writing proficiency and critical thinking. This research underscores the importance of a balanced approach to integrating AI tools in education, promoting both technological engagement and foundational skills development.